Hepatic fascioliasis in Mashhad, Northeast Iran: first report - Alireza Badirzadeh; Sadaf Sabzevari (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract Fascioliasis is a zoonotic disease caused by a leaf-like worm (fluke) called Fasciola. Herein, we present a case of human hepatic fascioliasis. A 57-year-old man was referred to the hospital for ambiguous gastrointestinal symptoms with suspected hemangioma. Hepatic fascioliasis was diagnosed using abdominal computed tomography and serology. He tested positive for the IgG antibody against Fasciola hepatica. The patient was treated successfully with triclabendazole. This is the first published report on the occurrence of fascioliasis in Northeast Iran, a non-endemic area for fascioliasis. Our results suggest the emergence of a new focus in the region.